The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1128/aac.02484-19
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally Engineered Mutations in a Ubiquitin Hydrolase, UBP-1, Modulate In Vivo Susceptibility to Artemisinin and Chloroquine in Plasmodium berghei

Abstract: As resistance to artemisinins (current frontline drugs in malaria treatment) emerges in Southeast Asia, there is an urgent need to identify the genetic determinants and understand the molecular mechanisms underpinning such resistance. Such insights could lead to prospective interventions to contain resistance and prevent the eventual spread to other regions where malaria is endemic. Reduced susceptibility to artemisinin in Southeast Asia has been primarily linked to mutations in the Plasmodium falciparum Kelch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(63 citation statements)
references
References 36 publications
11
50
0
Order By: Relevance
“…In earlier efforts to introduce UBP-1 mutations in PB, we found that pre-emptive drug pressure to which the engineered mutation is anticipated to confer protective advantage can selectively enrich for the mutant in a mixed, transfected parasite population even when the mutant population is <1% in the mixture (40). Using this approach, we subjected a larger inoculum (2 x 10 7 ) of the G2022 C592Y.1* , G2023 C592Y.2* , G2024 I555T* and G2025 R551T* lines to AS at 20 or 64 mg/kg to see if any enrichment in the recrudescent parasite populations could be achieved (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In earlier efforts to introduce UBP-1 mutations in PB, we found that pre-emptive drug pressure to which the engineered mutation is anticipated to confer protective advantage can selectively enrich for the mutant in a mixed, transfected parasite population even when the mutant population is <1% in the mixture (40). Using this approach, we subjected a larger inoculum (2 x 10 7 ) of the G2022 C592Y.1* , G2023 C592Y.2* , G2024 I555T* and G2025 R551T* lines to AS at 20 or 64 mg/kg to see if any enrichment in the recrudescent parasite populations could be achieved (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S3D) and sequencing. The V2721F UBP-1 mutant line, which we previously found to mediate reduced susceptibility to ARTs in PB (40), was also generated in the 1804cl1 background and cloned (Table S1). PB K13 mutants display reduced susceptibility to DHA in 24-hour assays and increased survival in PB-adapted RSAs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations